Unhealthy spin. Issue 7400 (29th May 2003) - Burton, Bob; Rowell, Andy
Abstract : Public relations companies are experts at "third party technique"—helping the drug industry separate the message from what could be seen as a self interested messenger. But most journalists have a sketchy idea about how the public relations industry works, and thereby are vulnerable to uncritically accepting the disguised messages of the drug industry